The Relationship between Self-Concept and Job Satisfaction on the Performance of Private High School Teachers - Puspitasari, Anjani; Widayatsih, Tri; Mulyadi, Mulyadi (Journal of Social Work and Science Education, 2024)
This study aims to find out and analyze: (1) The relationship between self-concept and teacher’s performance, (2) the relationship between job satisfaction and teacher’s performance, (3) the relationship between self-concept and job satisfaction together on teacher’s performance. This study is quantitative research with partial correlation and multiple correlation methods. This research was conducted at a private high school in Seberang Ulu 1 District, Palembang with 89 teacher respondents. Data collection techniques are in the form of questionnaires and documentation. The validity test uses the validity of the construct while the reliability test uses Cronbranch Alpha. The prerequisite test for analysis uses the normality test, linearity test, multicollinearity test and the data are analyzed using partial correlation analysis and multiple correlation followed by the t-test. The results of this study showed that there was a significant relationship between self-concept and job satisfaction on the performance of private high school teachers in Seberang Ulu 1 District, Palembang with a correlation value of 0.533, the simultaneous contribution or contribution of self-concept and job satisfaction variables to teacher’s performance was 28.4% while 71.6% was determined by other variables.